Stabilization of Peptide Vesicles by Introducing Inter-Peptide Disulfide Bonds - van Hell, Albert J. (Springer US, 2009)
PURPOSE: Previously, we have shown that the amphiphilic oligopeptide SA2 (Ac-Ala-Ala-Val-Val-Leu-Leu-Leu-Trp-Glu-Glu-COOH) spontaneously self-assemble into nano-sized vesicles in aqueous environment. Relative weak individual intermolecular interactions dominate such oligopeptide assemblies. In this study we aimed at improving the stability of such peptide vesicles by covalently crosslinking the oligopeptide vesicles using disulfide bonds. Two and three cysteines were introduced in the SA2 peptide sequence to allow crosslinking (Ac-Ala-Cys-Val-Cys-Leu-(Leu/Cys)-Leu-Trp-Glu-Glu-COOH). RESULTS: Upon disulfide formation the crosslinked vesicles remained stable under conditions that disrupted the non-crosslinked peptide vesicles. The stabilized vesicles were more closely examined in terms of particle size (distribution) using atomic force microscopy, cryogenic electron microscopy, as well as dynamic light scattering analysis, showing an average particle radius in number between 15 and 20 nm. Using entrapment of calcein it was shown that intermolecular crosslinking of peptides within the vesicles did not affect the permeability for calcein. CONCLUSION: Introduction of cysteines into the hydrophobic domain of the SA2 amphiphilic oligopeptides is a feasible strategy for crosslinking the peptide vesicles. Such small crosslinked oligopeptide vesicles may hold promise for drug delivery applications. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11095-009-9933-z) contains supplementary material, which is available to authorized users.